একুশের পটভূমি, একুশের স্মৃতি - রহমান, মতিউর, ১৯৪৬- (ঢাকা : প্রথমা প্রকাশন, 2011)
Contributed articles chiefly on the Bengali language movement of Bangladesh, 1952.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Bengali language movement; Language policy -- Bangladesh -- History; Bengali language -- Political aspects -- Bangladesh; Bangladesh -- Languages -- Political aspects